2015
DOI: 10.1080/10407782.2015.1052316
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Natural Convection in a Porous Cavity with Linearly Temperature Distributions Under the Local Thermal Nonequilibrium Condition

Abstract: A numerical investigation of the natural convection heat transfer in a rectangular cavity filled with a heat-generating porous medium by adopting the local thermal nonequilibrium (LTNE) model is reported in this paper. The top and bottom walls of the enclosure are adiabatic, the left wall is linearly cooled, and the right wall is cooled by a linear or uniform temperature profile. The results show that the isotherms for the fluid and solid phases become similar with the increase of the interphase heat transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The results showed that, compared with the uniform boundary conditions, the sinusoidal boundary conditions can enhance the heat transfer rate of a porous cavity. Wu et al (2015b) numerically investigated a two-dimensional steady-state fluid flow and heat transfer problem inside an enclosure filled with a heat-generating porous medium by linearly thermal boundary condition. The study used the generalized non-Darcy model to describe the flow field.…”
Section: Natural Convection Heat Transfermentioning
confidence: 99%
“…The results showed that, compared with the uniform boundary conditions, the sinusoidal boundary conditions can enhance the heat transfer rate of a porous cavity. Wu et al (2015b) numerically investigated a two-dimensional steady-state fluid flow and heat transfer problem inside an enclosure filled with a heat-generating porous medium by linearly thermal boundary condition. The study used the generalized non-Darcy model to describe the flow field.…”
Section: Natural Convection Heat Transfermentioning
confidence: 99%
“…The authors revealed that the overall heat transfer (Nusselt number) can be improved by imposing sinusoidal thermal boundary condition when compared to the case of a constant wall temperature. Wu et al [25] also analysed the effect non uniform wall temperature on the natural convection heat transfer in a cavity by considering a linear variation of the wall temperature. Other aspects of LTNE natural convection in a cavity, such as the effects of partially active wall with sinusoidal temperature [25], cavity aspect ratio [26], nanofluids [27] and cavity partially filled with porous media [28], have been addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well‐known fact that, owing to the widespread engineering applications, convective heat transfer in fluid‐saturated, heat‐generating porous enclosures has been a research topic of practical importance during the past three decades 1–10. Some of these applications are: management of radioactive waste storage, design and operation of nuclear reactor cores, cooling of electronic devices, design of chemical catalytic reactors, storage of agricultural and food products, etc.…”
Section: Introductionmentioning
confidence: 99%